EFFECT OF PENDING IN PENDING IN PARTICULAR PAD A PAJAH GEM OF DOUBLE CUT - Didik Nurhadiyanto (Jurnal Penelitian Saintek, 2010)
The purpose of this study, are (1) to compare the wear of a single cutter with a double cutter with the use of different  cooler  viscosity, (2)  to determine  the effect of cooller  viscosity  to cutter  wear,  and (3) find  a suitable  viscosity,  cooling  to reduce  cutter  wear.  The workpiece  material  is  VCN  150 ø 1.75  inches  with  a length of cut is 200 mm. Variables that are altered depth of cut. The depth of cut is defined  initial minus end diameter  divided  by two. The depth of cut for  a double edged pieces  with  a single piece. Cutter  wear  modifications   largest  taken from each  eye piece for  comparison  with  a single cutter.  Research  steps  undertaken were  as follows:   wear  to keep records  of each  viscosity  cooling,  ie 14.5 poise, poise 24.8, 35.6 poise,  and poise  while the depth of 49.2 pieces  0.5; 1; 1.5; and 2 mm. Each observation   performed 3 times and subsequently taken average. Comparing  the  wear  obtained  in cutting  using  single  and  double  cutting.  The results  of this study  are as follows: (1) a reduction  in the cutter  wear  double edged pieces  of 18.64% compared  with a single cutter with variable thickness and depth of cut cooling. (2) work without  cooling  wear  very  large,  so  that  liquid cooling is needed in the process  of cutting the workpiece, (3) become less viscous cooling is used, a reduction  in wear and tear on the range.  Wear and tear occurs in the thickness of the smallest 14.5 poise.Keywords: cooling, wear, and the depth of cut